Encyclopedia of Evolutionary Psychological Science 2017
DOI: 10.1007/978-3-319-16999-6_2447-1
|View full text |Cite
|
Sign up to set email alerts
|

Social Withdrawal in Childhood

Abstract: Socially withdrawn children frequently refrain from social activities in the presence of peers. The lack of social interaction in childhood may result from a variety of causes, including social fear and anxiety or a preference for solitude. From early childhood through to adolescence, socially withdrawn children are concurrently and predictively at risk for a wide range of negative adjustment outcomes, including socio-emotional difficulties (e.g., anxiety, low self-esteem, depressive symptoms, and internalizin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 107 publications
0
3
0
Order By: Relevance
“…The clinical psychology application of mindfulness has been altered and extended to many different fields through a variety of mindfulness courses, such as mindfulness workplace coaching (Ancona and Mendelson, 2014), childbirth and parenting (Duncan and Bardacke, 2010), competitive sports coaching (Scott-Hamilton et al, 2016), etc. Of all possible applications, school-based mindfulness that combines students' psychosomatic characteristics and traditional school mental health curricula has received the most attention (Yu and Wenjie, 2017). School-based mindfulness has been widely used in recent years to help a growing number of students suffering from mental health problems, such as anxiety (Essau et al, 2011), depression (Jellinek and Snyder, 1998), and social withdrawal (Hipson and Coplan, 2017). Previous studies have confirmed the value of mindfulness applications for improving schoolwork.…”
Section: Mindfulnessmentioning
confidence: 99%
See 1 more Smart Citation
“…The clinical psychology application of mindfulness has been altered and extended to many different fields through a variety of mindfulness courses, such as mindfulness workplace coaching (Ancona and Mendelson, 2014), childbirth and parenting (Duncan and Bardacke, 2010), competitive sports coaching (Scott-Hamilton et al, 2016), etc. Of all possible applications, school-based mindfulness that combines students' psychosomatic characteristics and traditional school mental health curricula has received the most attention (Yu and Wenjie, 2017). School-based mindfulness has been widely used in recent years to help a growing number of students suffering from mental health problems, such as anxiety (Essau et al, 2011), depression (Jellinek and Snyder, 1998), and social withdrawal (Hipson and Coplan, 2017). Previous studies have confirmed the value of mindfulness applications for improving schoolwork.…”
Section: Mindfulnessmentioning
confidence: 99%
“…Of all possible applications, school-based mindfulness that combines students' psychosomatic characteristics and traditional school mental health curricula has received the most attention (Yu and Wenjie, 2017 ). School-based mindfulness has been widely used in recent years to help a growing number of students suffering from mental health problems, such as anxiety (Essau et al, 2011 ), depression (Jellinek and Snyder, 1998 ), and social withdrawal (Hipson and Coplan, 2017 ). Previous studies have confirmed the value of mindfulness applications for improving schoolwork.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Social withdrawal, as a temperamental characteristic, has been found to predict negative psychosocial outcomes, including behaviour problems later in childhood and adolescence (e.g. Chronis-Tuscano, Danko, Rubin, Coplan, & Novick, 2018;Hipson & Coplan, 2018;Quinn & Harden, 2013;Rubin et al, 2009). Social withdrawal may arise from social fear as well as internal factors, e.g.…”
Section: The Joint Effects Of Social Withdrawal and Socioemotional Dementioning
confidence: 99%